2011
DOI: 10.1093/jxb/err237
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of Pennisetum glaucum vacuolar Na+/H+ antiporter and Arabidopsis H+-pyrophosphatase enhances salt tolerance in transgenic tomato

Abstract: Salinity is one of the major abiotic stresses affecting plant productivity. Tomato (Solanum lycopersicum L.), an important and widespread crop in the world, is sensitive to moderate levels of salt in the soil. To generate tomato plants that can adapt to saline soil, AVP1, a vacuolar H(+)-pyrophosphatase gene from Arabidopsis thaliana, and PgNHX1, a vacuolar Na(+)/H(+) antiporter gene from Pennisetum glaucum, were co-expressed by Agrobacterium tumefaciens-mediated transformation. A sample of transformants was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 38 publications
6
39
1
Order By: Relevance
“…(Bhaskaran and Savithramma 2011). In the present investigation, we observed a better germination rate and growth of TaNHX2-transgenic seeds compared to wild type (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…(Bhaskaran and Savithramma 2011). In the present investigation, we observed a better germination rate and growth of TaNHX2-transgenic seeds compared to wild type (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Many reports have been published on the metabolic engineering of salt tolerance in tomato using various genes (Goel et al 2010(Goel et al , 2011Choi et al 2011). However, only a few reports have been published on genetic engineering of tomato using NHX proteins to improve salt stress tolerance Rodríguez-Rosales et al 2008;Bhaskaran and Savithramma 2011).…”
Section: Introductionmentioning
confidence: 99%
“…antiporter, which increase tolerance to salinity. The data presented by Bhaskaran and Savithramma (2011) and Yarra et al (2012) support the aforementioned hypothesis. Some research has indicated a significant role for vacuolar H ?…”
Section: Applicable Tomato Transformationsupporting
confidence: 75%
“…against a concentration gradient) across plant cell membranes (plasmalemma and tonoplast) is usually coupled to the proton (H + ) electrochemical potential established by H + -translocating pumps. The vacuolar Na + /H + antiporter and H + -pyrophosphatase pump (H + -PPase) are genotype dependent and confer tolerance to salinity (Goel et al, 2010;Bhaskaran et al, 2011). Additionally, resistant crops benefit from the higher capacity of K + -Na + homeostasis.…”
Section: Differential Responses Of Genotypes To Salinity Levels and Nmentioning
confidence: 99%